Molecular structure, vibrational spectroscopic and HOMO/LUMO studies of some organotellurium compounds by quantum chemical investigations - Al-Asadi, Rafid Hmedan; Saeed, Bahjat Ali; Fahad, Tarik Ali (European Journal of Chemistry, 2015)
Quantum mechanical calculations of geometries, energies and vibrational frequencies of organic mercury and tellurium compounds containing azomethine group, molecules a1-a5 and containing azo group, molecules a6-a10 have been undertaken using density functional theory. The optimized geometrical parameters such as bond lengths, bond angles and dihedral angles showed that only organomercuric compounds have planer structures. The calculation of the total energy and HOMO-LUMO energy gap were showed that organotellurium compounds have higher reactivity than the corresponding organomercuric compounds. As well it showed the HOMO orbitals are localized mainly on tellurium, nitrogen and bromine atoms moieties, while the LUMO of π nature are mostly located on the phenyl ring. The calculated vibrational frequencies of molecules a1 and a7 are in good agreement with experimental frequencies with correlation coefficient r2 value is 0.9875 and 0.9987, respectively.